1992
DOI: 10.1590/s0074-02761992000700033
|View full text |Cite
|
Sign up to set email alerts
|

New methods for the diagnosis of Babesia bigemina infection

Abstract: Accurate diagnosis of Babesia bigemina infection, an economically important tick-transmitted protozoan parasite of cattle, is essential in the management of disease control and in epidemiological studies. The currently used methods of diagnosis are blood smear examination and serological tests which include agglutination and immunofluorescence tests. These tests have been used in the fild but because they lack sensitivity and specificity, newer and improved methods of diagnosis are being developed. The quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Cross-reaction of antibodies to B. bovis is an added complication in regions where the two parasites occur simultaneously (Morzaria et al 1992; de Vos and Jorgensen 1996). Enzyme-linked immunosorbent assays (ELISAs) have been successfully developed for the detection of antibodies to other Babesia species (Wright 1990;BoÈ se et al 1995), but several complicating factors have impeded the development of an assay for B. bigemina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-reaction of antibodies to B. bovis is an added complication in regions where the two parasites occur simultaneously (Morzaria et al 1992; de Vos and Jorgensen 1996). Enzyme-linked immunosorbent assays (ELISAs) have been successfully developed for the detection of antibodies to other Babesia species (Wright 1990;BoÈ se et al 1995), but several complicating factors have impeded the development of an assay for B. bigemina.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews by Palmer (1991), Morzaria et al (1992) and El-Ghaysh et al (1996) have concluded that a sensitive and speci®c test for antibodies to B. bigemina would require puri®ed antigen and/or monoclonal antibodies (MoAbs). Morzaria et al (1992) described an ELISA based on a 200-kDa parasite antigen that was in the early stage of development, but that assay required the use of antigen-and antibody-detection ELISAs together to improve its sensitivity beyond that of the IFAT. In a recent review of serological tests for diagnosis of babesiosis, BoÈ se et al (1995) concluded that existing serological tests for B. bigemina were inadequate and that the development of an improved test was a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Informações sobre a epidemiologia de doenças transmitidas por carrapatos, especialmente sobre a dinâmica de transmissão da infecção por este vetor, são essenciais para elaboração de eficientes estratégias de controle (Morzaria et al 1992). No Brasil, escassos estudos têm sido realizados utilizando carrapatos na detecção da infecção por Babesia spp.…”
Section: Resultsunclassified
“…Other serological methods that have been developed and utilized in the past include an indirect immunofluorescence assay (6) and a number of ELISA-based formats (4,17). Although these assays allow the detection of infected cattle, they all have limitations in specificity, sensitivity, and reliability to some degree; and the indirect immunofluorescence assay requires subjective interpretation and low throughput.…”
Section: Discussionmentioning
confidence: 99%